2002
DOI: 10.1143/jpsj.71.1313
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Structural Properties of Ti4AlN3Investigated byAb initioCalculations

Abstract: The crystal structure, electronic structure and chemical bonding of Ti 4 AlN 3 have been investigated by ab initio pseudopotential calculations. The equilibrium lattice parameters, atomic positions in the unit cell and bond lengths have been obtained by minimizing the total energy. The differences between the calculated and measured lattice constants are generally less than 1%. The electronic structure of Ti 4 AlN 3 shows a metallic-like character and the 3d states of Ti dominate its electronic conductivity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In Fig. 4, the relative stability of Ti 3 AlN polymorphic phases is demonstrated by comparing the minimum Gibbs 9 3.370 11.497, 9 11.553 8.939, 9 9.011 Experiment 3.369 15 11.498 15 8.983 15 o-Hf 3 AlN PAW-PBE 3.340, 9 3.315 11.393, 9 11.385 8.886, 9 8.885 Experiment 3.319, 16 3.302 7 11.326, 16 11.347 8 8.865, 16 8.850 8 free energies at each temperature. The Gibbs free energies of o-Ti 3 AlN and c-Ti 3 AlN phases cross at around 1255 K. Therefore, the correction on phase transition temperature is only 7 K after the improvement from harmonic to quasiharmonic approximations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Fig. 4, the relative stability of Ti 3 AlN polymorphic phases is demonstrated by comparing the minimum Gibbs 9 3.370 11.497, 9 11.553 8.939, 9 9.011 Experiment 3.369 15 11.498 15 8.983 15 o-Hf 3 AlN PAW-PBE 3.340, 9 3.315 11.393, 9 11.385 8.886, 9 8.885 Experiment 3.319, 16 3.302 7 11.326, 16 11.347 8 8.865, 16 8.850 8 free energies at each temperature. The Gibbs free energies of o-Ti 3 AlN and c-Ti 3 AlN phases cross at around 1255 K. Therefore, the correction on phase transition temperature is only 7 K after the improvement from harmonic to quasiharmonic approximations.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive researches on damage tolerant carbides and nitrides provided sound scientific and technological bases for their applications as advanced high‐temperature structural materials. The identified damage tolerant ceramics, such as M n +1 AX n phases (M is an early transition metal, A is an A‐group element, and X is either C or N), typically possess layered crystal structures and heterogeneous chemical bonding . Recently, nanolaminated nitrides M 3 AlN with the orthorhombic crystal structure (o‐Zr 3 AlN and o‐Hf 3 AlN) were reported with the optimal combination of good damage tolerance and excellent high‐temperature mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information derived from these SAED and CBED patterns indicated that Ta 4 AlC 3 crystallized in the space group P6 3 /mmc. Most layered ternary compounds have the space group P6 3 /mmc, e.g., Ti 2 AlC, 10 Ti 4 AlN 3 , 22,23 and Ti 3 AlC 2 . 9,24 For materials with P6 3 mc space group, no mirror plane will be observed perpendicular to the 6-fold axis, which is shown in the CBED pattern of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The deformation and failure modes for Ti 2 AlN were studied via firstprinciples density functional calculations [11]. The crystal structure, electronic structure, and chemical bonding of Ti 4 AlN 3 were investigated by ab initio pseudopotential calculations [12]. Li et al [13] studied the dielectric functions and reflectivity spectra of Ti 4 AlN 3 by first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%